Optimization of protein yields by ultrasound assisted extraction from Eurycoma longifolia roots and effect of agitation speed - Elhag, Husam Eldin Elhag Abugabr; Nailaa, Aishath; Nour, A. H.; Azilah, Ajit; Ahmad Ziad, Sulaiman; Badhrulhisham, Abdul Aziz (King Saud University, 2019)
The traditional ways of protein extraction is disadvantageous from both economic and environment perspective. In this study, ultrasonic assisted extraction, UAE technique was used for the first time for the optimization process of extracting proteins from Eurycoma longifolia roots. The experiments demonstrated the successful effect of applying eccentric agitation with UAE to provide a combination of agitation and sonication to extract the proteins in short extraction times. Central composite design (CCD) was used to optimize the Ultrasonic-assisted extraction of proteins from roots of Eurycoma longifolia by water. Response surface methodology (RSM) was employed to investigate the effects of five independent variables; particle sizes (A), extraction temperatures (B), agitation speeds (C), amplitude (D) and duty cycle (E). The second enhanced model (Y2) prevailed to be more efficient in protein recovery with optimum conditions of A: 0.022 ± 0.022 mm, B: 49 °C, C: 1314 rpm, D: 9 W and E: 63% UI: 2.94 W·cm−2 was 9.543 ± 0. 946%. High agitation speed didn’t only affect the solvent properties, the diffusion of the solutes from the particles, cooling the extraction temperature, but influenced the distribution of cavitation bubbles and their impact on the solid particles. UAE was found to minimize the extraction of the same amount by conventional extraction 7-fold times. The results obtained in this study have exposed the capability of ultrasonic assisted extraction, UAE technology in extraction of protein from E. longifolia roots. Further works are nevertheless required to provide deeper understanding of the mechanisms involved to facilitate the development of optimum system applicable to the industry.